2021
DOI: 10.24191/jeeir.v9i2.13212
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Nigerians to invest in Sukuk for infrastructure development

Abstract: This study investigates the factors influencing the intention to invest in Sukuk towards infrastructural development in Nigeria. The study used a quantitative research approach and obtained data through survey method and online questionnaires. Data were obtained in Abuja, the capital of Nigeria, from 163 investors and potential investors in Sukuk. The result revealed that attitude, subjective norms, perceived behavioral control, and religiosity have a positive significant relationship with intention to invest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Moreover, social influence profoundly impacts Muslims' intentions to invest in Hajj funds (Setyawan et al, 2020). The collective responsibility, cultural norms, social recognition and spiritual rewards associated with Marketing halal investment contributing to the pilgrimage of fellow Muslims play a pivotal role in motivating individuals to participate in Hajj funds (AbdulKareem et al, 2021). In addition, many scholars, such as Bin-Nashwan and Muneeza (2021), confirmed that social norms have positively driven customers' intentions to invest in Islamic Sukuk in Malaysia.…”
Section: Literaturementioning
confidence: 99%
“…Moreover, social influence profoundly impacts Muslims' intentions to invest in Hajj funds (Setyawan et al, 2020). The collective responsibility, cultural norms, social recognition and spiritual rewards associated with Marketing halal investment contributing to the pilgrimage of fellow Muslims play a pivotal role in motivating individuals to participate in Hajj funds (AbdulKareem et al, 2021). In addition, many scholars, such as Bin-Nashwan and Muneeza (2021), confirmed that social norms have positively driven customers' intentions to invest in Islamic Sukuk in Malaysia.…”
Section: Literaturementioning
confidence: 99%
“…Belief control is based on the individual's experience about the behaviour, information about behaviour, and various other things that can influence the individual's opinion about the ease or difficulty in performing certain behaviours. Meanwhile, the perceived power of control is an individual's assumption about how strong he feels about each of the factors that support and inhibit the behaviour (Ajzen, 2005), the perception referred to in this study is retail investors' expectations in external and internal constraints about the ease of accessing SME's sukuk investment (Warsame & Ireri, 2016;AbdulKareem et al, 2021;Awadh et al, 2022).…”
Section: Perceptions Of Behavioural Controlmentioning
confidence: 99%
“…Also, Amin et al, (2011) described religious as the role that influences an individual's activities and decision. It is acknowledged that individual option to participate in Sukuk investment can be influenced by the fact that this kind of investment offered is corresponding to Islamic law, AbdulKareem et al (2021) found that the level of religious surrounded within-person as a factor of an individual's intention to involve in Sukuk investment. In the context of this study we observed what is the role of one's religious observance in influencing attitudes towards SME's sukuk investment (Ashidiqi & Arundina, 2017).…”
Section: Religious Factormentioning
confidence: 99%
See 1 more Smart Citation
“…This can attract Islamic investors who are looking for sharia-compliant investment opportunities and can provide an alternative source of funding for infrastructure projects (Usmani, 2021) One of the ways in which Islamic finance can be used to finance infrastructure projects is using sukuk (Islamic bonds). Sukuk are shariacompliant financial instruments that are like conventional bonds, but instead of paying interest, sukuk holders share in the profits of the underlying assets (AbdulKareem and Mahmud, 2019). This makes them an attractive option for infrastructure project finance as they align the interests of investors with the performance of the project.…”
Section: Islamic Project Financementioning
confidence: 99%